An Uncharacterized Major Facilitator Superfamily Transporter From Planococcus maritimus Exhibits Dual Functions as a Na+(Li+, K+)/H+ Antiporter and a Multidrug Efflux Pump - Abdel-Motaal, Heba; Meng, Lin; Zhang, Zhenglai; Abdelazez, Amro H.; Shao, Li; Xu, Tong; Meng, Fankui; Abozaed, Shaima; Zhang, Rui; Jiang, Juquan (Frontiers in Microbiology, 2018)
Within major facilitator superfamily (MFS), up to 27 unknown major facilitator families and many members of 60 well-characterized families have been functionally unknown as yet, due to their sharing no or significantly low sequence identity with characterized MFS members. Here we present the first report on the characterization of one functionally unknown MFS transporter designated MdrP with the accession version No. ANU18183.1 from the slight halophile Planococcus maritmus DSM 17275T. During the screening of Na+/H+ antiporter genes, we found at first that MdrP exhibits Na+(Li+, K+)/H+ antiport activity, and propose that it should represent a novel class of Na+(Li+, K+)/H+ antiporters. However, we speculate that MdrP may possess an additional protein function. The existence of the signature Motif A of drug/H+antiporter (DHA) family members and phylogenetic analysis suggest that MdrP may also function as adrug efflux pump, which was established by minimum inhibitory concentration tests and drug efflux activity assays. Taken together, this novel MFS transporter exhibits dual functions as a Na+(Li+, K+)/H+ antiporter and a multidrug efflux pump, which will be very helpful to not only positively contribute to the function prediction of uncharacterized MFS members especially DHA1 family ones, but also broaden the knowledge of Na+/H+ antiporters.